Impact the shear connector properties on the behavior of steel–concrete-steel sandwich beams. (2022) - Mhalhal, Jasim M.; Alawsi, Manal A.; Al-Gasham, Thaar S.; Abid, Sallal R.
Abstract: This paper describes the behavior of steel–concrete-steel sandwich beams with new configuration of shear connector. Five sandwich beams composed of a normal concrete core that was filled between a pair of 4 mm steel skin plates were prepared and tested under three-point loading up to failure. The truss shear connectors were formed from vertical and diagonal elements with different diameters of 10, 12 and 16 mm and different spacing of 100, 200, and 250 mm. All beams had a cross section of 100 × 200 mm, with a total length of 1200 mm. Results indicated that ultimate load capacity increased by about approximately 32 and 43 % with the increase of shear connectors diameter by 20 and 60%, respectively. In addition, raising the spacing of the shear connectors by 100% led to a reduction in the ultimate load capacity by approximately 31 and 68%, respectively. The test results also confirmed that when the shear connectors diameter was increased from 10 to 12 and 16 mm, the ductility index, service stiffness and flexural toughness improved by approximately 23 and 155 %, 17 and 34 % and 26 and 382 %, respectively.